Desenvolvimento de uma ferramenta computacional para tomada de decisão na avaliação de projetos : aplicação em habitação de interesse social - Moraes, Amauri Gomes de (2006)
To apply a model to evaluate and to compare the projects of habitations of social interest on the basis of the relation between the cost perceived for the market and the performance of the localization attributes, of physical structure and infrastructure, consists inside in a challenge of the diverse and peculiar nature of the classes of lesser wage income of the society. The deficit of the habitation in Brazil, the satisfaction lack in the acquisition of real properties, whose attributes do not play its functions satisfactorily, the infrastructure lack and the necessity to minimize the social problem caused by the deficit of the habitation, is the reasons to develop the research in this area. This context considers to give emphasis to develop a computational tool, to identify together to the users of habitations of social interest the attributes most excellent of the construction and that they make possible to evaluate the project, to apply the model of evaluation and comparison of projects on the basis of the value and, for the analysis statistics, to define the minimum size of a sample and e that brings resulted acceptable of the application of software. The research was carried through, initially, with the identification of the projects of habitations yielded by the Secretariat of Habitation of the Passo Fundo city and, in the sequence, had been identified to the attributes most excellent, defined the criteria for the choice of the population-target and carried through the interviews; finally, it was developed and applied the computational tool for evaluation of projects in the social class in study. The first results had come for the application of the model in spread sheets and, later, for the development of the software, which, besides speeding the attainment of the results, stores the data for future consultations and analyses. Between the main conclusions are distinguished it possibility of applying the model of evaluation and comparison of projects for the users of habitations of social interest with the attainment of favorable results for reanalyze of the projects and the fast verification of the results by means of the use of the computational tool. With the improvement, the computational tool could be applied in other market-target, as well as in other products